The real experience with women's hysterectomy: A meta‐synthesis of qualitative research evidence - Na Li; Chen Shen; Rao Wang; Zhiping Chu (Wiley, 2023)
Abstract Aim The aim of this meta‐synthesis was to identify and synthesize qualitative research evaluating the real feelings, inner needs and emotional experience of women undergoing hysterectomy. Design Meta‐synthesis. Methods The PubMed, Web of Science, Cochrane Library, CINAHL, Embase, Ovid Medline and Sino Med were systematically searched until November 2021 and updated until June 2022. Two reviewers independently extracted data into a Microsoft Excel sheet. Qualitative meta‐synthesis was performed by coding relevant citations, organizing codes into descriptive themes and developing analytical themes. Results Qualitative meta‐synthesis yielded three themes and nine sub‐themes: comprehensive consideration before hysterectomy (a. disease factors; b. fertility factors; c. opinions of others); emotions and experience after hysterectomy (a. postoperative physical condition; b. psychological resilience to the loss of the uterus; c. changes in the couple's relationship); coping strategies (a. self‐denial and avoidance; b. change of perception and self‐adjustment; c. seek help from others).